2018
DOI: 10.1101/274704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fractionated follow-up chemotherapy delays the onset of resistance in bone metastatic prostate cancer

Abstract: Prostate cancer to bone metastases are almost always lethal. This results from the ability of metastatic prostate cancer cells to co-opt bone remodeling leading to what is known as the vicious cycle. Understanding how tumor cells can disrupt bone homeostasis through their interactions with the stroma and how metastatic tumors respond to treatment is key to the development of new treatments for what remains an incurable disease. Here we describe an evolutionary game theoretical model of both the homeostatic bon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As original replicator dynamics ( 7) assume that n i=1 q i = 1, extensions have been made to capture situations with a varying total population size. Such extensions involve fictitious freespace strategies [108,192], but also more general dynamics [101,123,186]. A relatively large body of literature models interactions between cancer cells of different types and/or interactions between cancer cells and the environment through the Lotka-Volterra (LV) competition equations and their extensions [30,55,75,206].…”
Section: Lotka-volterra Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As original replicator dynamics ( 7) assume that n i=1 q i = 1, extensions have been made to capture situations with a varying total population size. Such extensions involve fictitious freespace strategies [108,192], but also more general dynamics [101,123,186]. A relatively large body of literature models interactions between cancer cells of different types and/or interactions between cancer cells and the environment through the Lotka-Volterra (LV) competition equations and their extensions [30,55,75,206].…”
Section: Lotka-volterra Modelsmentioning
confidence: 99%
“…Warman et al focused on a fitness matrix model of the vicious cycle of metastatic prostate cancer cells co-opting bone remodeling [192]. The authors introduced fractionated follow-up therapy-chemotherapy where dosage is administered initially in one solid block followed by alternating smaller doses and holidays-and showed that it is better than either a continuous application or a periodic one.…”
Section: Physician Optimizing Objectives Other Than Reaching the Ess While Cancer Cells Are In Their Transient Phasementioning
confidence: 99%
“…As the replicator dynamics ( 9) include frequency dynamics only and cannot capture the changes of cancer cell population, alternative modeling frameworks have been adopted to capture both ecological and evolutionary dynamics of cancer cells. These include expanding replicator dynamics by additional population dynamics elements, such as through fictious free-space strategies [104,187], but also different models capturing population dynamics directly [119,180]. A relatively large body of literature models interactions between cancer cells of different types and/or interactions between cancer cells and the environment through the Lotka-Volterra competition equations and their extensions [29,52,72,200].…”
Section: Lotka-volterra Modelsmentioning
confidence: 99%
“…They adopted optimal control theory and showed analytically that to reduce the tumor volume while preserving its heterogeneity, one needs to apply lower than the MTD of drugs. Warman et al (2018) focused on a fitness matrix model of the vicious cycle of metastatic prostate cancer cells co-opting bone remodeling [187].…”
Section: 2mentioning
confidence: 99%
“…Student projects contributed to a number of peer-reviewed and published articles and book chapters in topical and interdisciplinary journals including PLoS Computational Biology [38], Scientific Reports [39], International Journal of Radiation Biology [40], Games [41], Annals of Epidemiology [42], and Encyclopedia of Biomedical Engineering [43], as well as several BioRxiv preprints [4447].…”
Section: Introductionmentioning
confidence: 99%